What are people eating in Surkhet, Nepal? Food consumption, food security, food sources, and food perceptions - Scott, Samuel P.; Patwardhan, Sharvari; Chakrabarti, Suman; Chauhan, Alka; Banerjee, Archis; Neupane, Sumanta; Parvin, Aklima; Rasheed, Sabrina; Afsana, Kaosar; Shaheen, Nazma; Blake, Christine; Menon, Purnima; et al. (CGIAR, 2023)
The Transforming Agrifood Systems in South Asia (TAFSSA) district agrifood systems assessment aims to provide a reliable, accessible, and integrated evidence base that links farm production, market access, dietary patterns, climate risk responses, and natural resource management with gender as a cross-cutting issue in rural areas of Bangladesh, India, and Nepal. It is designed to be a district-level multi year assessment. Using data collected in March-April 2023, this data note describes what people are eating, where they get their food, household food insecurity, and perceptions about food. This is one of a set of data notes that, together, provide a holistic picture of the agrifood system in the district.